Blow-up of solutions of a logarithmic flexible structure system with second sound in the presence of delay term in time - Attia, Salah Eddine, Auteur; Merah, Ahlem; Merah, Ahlem, Directeur de thèse. - Laghouat : Université Amar Telidji - Département de mathématiques, (Laghouat : Université Amar Telidji - Département de mathématiques, 2025)
The main objective of this work is the study of the Blow-up of solutions to a Logarithmic Flexible Structure system with Second Sound in the presence of delay term in time. This work is composed of two chapters with general introduction and bibliography. The first chapter deals with the preliminary notions on the theory of functional spaces, and some theorems and inequalities used in this research. In the second chapter: we first use the multiplier method to find the energy functional then by using the direct method of Georgiev and Todorova we proved that the solution blows-up in a finite time.